Photonics Breakthroughs 2024: Lithium-Niobate Photonics for Dense Wavelength-Division Multiplexing - Hongxuan Liu; Mingyu Zhu; Liu Liu; Daoxin Dai (IEEE Photonics Journal)
The growing demands for ultrahigh-capacity data transmission require advanced multiplexing for multiple channels together with high-speed modulation. The dense wavelength-division multiplexing (DWDM) technology has been widely utilized over the past few decades, while lithium-niobate-on-insulator (LNOI) has recently shown significant benefits for high-speed electro-optic modulation. However, the implementation of DWDM components on x-cut LNOI faces challenges due to material anisotropy and structural asymmetry. This paper highlights recent breakthroughs in x-cut LNOI photonic transmitters and filters for DWDM systems, focusing on cascaded multimode Fabry-Perot cavities and anisotropy-free arrayed waveguide gratings. These innovative photonic devices, along with their excellent performance, strengthen LNOI photonics to be compelling for the development of multifunctional photonic integration available for high-capacity optical data transmission and optical signal processing.